Effectiveness of Social Media Dissemination to Increase Children's Participation in Covid Vaccines - Arifah Salastiani Intan; Nurul Lutfia Maryadi; Raniah Tamarisha (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2021)
This research is entitled "Effectiveness of Social Media Outreach to Increase Children's Participation in the Covid Vaccine." This study aims to determine the effectiveness of social media as propaganda in increasing the number of children's participation in the Covid-19 vaccine. Respondents started from the age of 15-17 years. The object of this research is children who use social media. This study uses a quantitative approach. The sampling technique in this study used random sampling. The number of participants involved was 100 respondents in the form of data used as a questionnaire with a Likert scale to analyze the data. The results of this study found that: 1.) Disseminating information on COVID-19 vaccines to children on social media was very effective, with 88% results. 2.) Sharing information on the covid-19 vaccine makes children confident to do the vaccine with 92% results. 3.) Respondents agree that information on the Covid-19 vaccination policy in Indonesia through social media is easy to find with the result, which is 100%.